Corrosion Inhibition of Deposited Steels in the Presence of Bacteria - Suarez-Rodriguez, Erika (Curtin University, 2019)
Deposits and microorganisms represent a threat to internal pipeline integrity. The research fields of microbiologically influenced corrosion (MIC), under-deposit corrosion (UDC) and UDC inhibition were integrated to study under-deposit microbial corrosion (UDMC). The performance of corrosion inhibitors on carbon steel covered with different deposits was evaluated. UDMC research was conducted in the presence of a bacterial isolate and an oilfield microbial consortium. A multidisciplinary approach was developed and applied to investigate UDMC and its inhibition.